The expression profile of ATP-binding cassette transporter genes in breast carcinoma - Hlaváč, Viktor; Brynychová, Veronika; Václavíková, Radka; Ehrlichová, Marie; Vrána, David; Pecha, Václav; Koževniková, Renata; Trnková, Markéta; Gatěk, Jiří; Kopperová, Dana; Gut, Ivan; Souček, Pavel (Pharmacogenomics, 2013)
AIM: ATP-binding cassette (ABC) transporters contribute to development of resistance to anticancer drugs via ATP-dependent drug efflux. A major goal of our study was to investigate associations between the expression of ABC transporters and outcome of breast carcinoma patients. PATIENTS & METHODS: Transcript levels of all 49 human ABC transporters were determined in post-treatment tumor and non-neoplastic tissue samples from 68 breast carcinoma patients treated by neoadjuvant chemotherapy. Six ABC transporters were then evaluated in independent series of 100 pretreatment patients. RESULTS: ABCA5/6/8/9/10, ABCB1/5/11, ABCC6/9, ABCD2/4, ABCG5 and ABCG8 were significantly downregulated and ABCA2/3/7/12, ABCB2/3/8/9/10, ABCC1/4/5/10/11/12, ABCD1/3, ABCE1, ABCF1/2/3 and ABCG1 were upregulated in post-treatment tumors compared with non-neoplastic tissues. Significant associations of intratumoral levels of ABCC1 and ABCC8 with grade and expression of hormonal receptors were found in both sets of patients. ABCA12, ABCA13 and ABCD2 levels were significantly associated with the response to neoadjuvant chemotherapy in post-treatment patients. Protein expression of ABCA12, ABCC8 and ABCD2 in tumor tissues of patients with breast carcinoma was observed by immunoblotting for the first time. CONCLUSION: ABCA12, ABCA13, ABCC1, ABCC8 and ABCD2 present potential modifiers of progression and response to the chemotherapy of breast carcinoma.
Keywords: regulace genové exprese u nádorů; ATP-Binding Cassette Transporters; nádory prsu; Neoadjuvant Therapy; Female; ženské pohlaví; neoadjuvantní terapie; Gene Expression Regulation, Neoplastic; lidé; ABC transportéry; Antineoplastic Agents; Gene Expression Profiling; protinádorové látky; Breast Neoplasms; Carcinoma; stanovení celkové genové exprese; karcinom; genetické asociační studie; lidé středního věku; Middle Aged; Genetic Association Studies; Humans